More than just a side effect: Dynamic knee valgus and deadbug bridging performance in youth soccer players and alpine skiers have similar absolute values and asymmetry magnitudes but differ in terms of the direction of laterality - Hanimann, Jonas; Ellenberger, Lynn; Bernhard, Thomas; Franchi, Martino V.; Roth, Ralf; Faude, Oliver; Spörri, Jörg (Frontiers in Physiology, 2023)
From a preventative perspective, leg axis and core stabilization capacity are important for soccer players and alpine skiers; however, the role of laterality differs in these sports. The aims of this study were (1) to determine whether there are differences in leg axis and core stability between youth soccer players and alpine skiers, (2) between dominant and nondominant sides and (3) to explore the outcomes of applying common sport-specific asymmetry thresholds to these two distinct cohorts. Twenty-one highly trained/national level c soccer players (16.1 years, 95% CI: 15.6, 16.5) and 61 alpine skiers (15.7 years, 95% CI: 15.6, 15.8) participated in this study. Using a marker-based 3D motion capture system, dynamic knee valgus was quantified as the medial knee displacement (MKD) during drop jump landings, and core stability was quantified as the vertical displacement during deadbug bridging exercise (DBBdisplacement). For the analysis of sports and side differences, a repeated-measures multivariate analysis of variance was used. For the interpretation of laterality, coefficients of variation (CV) and common asymmetry thresholds were used. There were no differences in MKD or DBBdisplacement between soccer players and skiers or between the dominant and nondominant sides, but there was an interaction effect side*sports for both variables (MKD: p = 0.040, partial eta2 = 0.052; DBBdisplacement: p = 0.025, partial eta2 = 0.061). On average, MKD was larger on the nondominant side and DBBdisplacement laterality to the dominant side in soccer players, whereas this pattern was reversed in alpine skiers. Despite similar absolute values and asymmetry magnitudes of dynamic knee valgus and deadbug bridging performance in youth soccer players and alpine skiers, the effect on the direction of laterality was opposite even though much less pronounced. This may imply that sport-specific demands and potential laterality advantages should be considered when dealing with asymmetries in athletes.